(untitled) (Research, Society and Development, 2022)
Menopausal women experience estrogen deficiency during this period, which causes vasomotor symptoms such as mood swings, hot flushes, palpitations, headache, irritation, and depression. There are several pharmacological treatments as well as the use of dietary supplements to control these clinical manifestations, however therapies from medicinal plants have been highlighted, among them Trifolium pratense L. Popularly known as Red clover, it has a record in the Therapeutic Memento and in the Anvisa’s Herbal Medicines Form, being considered a therapeutic adjunct in the treatment of climacteric. An integrative and narrative review using the Cochrane Central Register of Controlled Trials (CENTRAL), Cumulative Index for Nursing and Allied Health Literature (CINAHL; www.ebscohost.com/cinahl/), Embase, PubMed, LILACS, MEDLINE, PsycINFO and Web of Science as keywords adopted: “Trifolium pratense”, “clinical trial” and “hot flashes”. As a complement to the review, protocols for studies and ongoing trials were searched on CriticalTrials.gov. What resulted after analysis of the articles, 7 records. It is noted that the plant species studied exhibits a wealth of isoflavones in its composition, these metabolites are considered selective modulators of estrogen receptors, and can act as agonist and antagonist of estrogen receptors. Significant results were observed with Trifolium pratense in relieving hot flashes in women, however further trials are needed to safely define this clinical practice.